Synthesis, characterization and application of a novel biosorbent-magnetic nanomaterial cross-linked with cyclodextrin using epichlorohydrin and hexamethylene diisocyanate as adsorbents for heavy metals and organics - Pholosi, Agnes (Vaal University of Technology, 2019)
In the present era of water resources scarcity, efficient treatment of wastewater is a major prerequisite especially for growing economy. Numerous approaches have been studied for the development of cheaper and more effective adsorbents for removal of both organic and inorganic pollutants from wastewater. The present study seeks to harness the potential of biosorption and nanotechnology by producing more efficient, selective, mechanically stable and effective adsorbents for removal of organic and inorganic pollutants. The biosorbent-magnetic nanomaterial was synthesized by coating magnetite nanoparticles with sodium hydroxide treated pine cone by co-precipitation method. Magnetite coated pine bio-composite was then modified by cross-linking with hexamethylene diisocyanate and epichlorohydrin to the molecular recognition compound “cyclodextrin”. These novel biosorbent-magnetic nanoparticle materials were explored in overcoming the drawbacks of the biosorbent alone and selectively remove inorganic and organic pollutants from complex matrices. The synthesized materials were characterized by several analytical techniques including, Fourier Transformed Infrared Spectroscopy (FTIR), Thermogravimetric analysis (TGA), X-Ray Diffraction (XRD), Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM–EDX), Transmission Electron Microscopy (TEM), Brunauer, Emmett and Teller Isotherm (BET) surface area analysis, X-ray Photoelectron Spectroscopy (XPS), Vibrating Sample Magnetometer (VSM) and pH at point of zero charge (pHpzc). Sodium hydroxide treated pine cone and magnetite coated pine cone were applied for both chromium(VI) and arsenic(III) adsorption while the magnetite coated pine cone, magnetite coated pine cone crosslinked to cyclodextrin using both epichlorohydrin and hexamethylene diisocyanate were applied for 4-nitrophenol removal from aqueous solution. Batch adsorption studies were performed to optimize operating parameters such as solution pH, adsorbent dose, contact time, temperature and initial concentration. Pseudo first, pseudo second, intraparticle diffusion, pore and film diffusion kinetic models were determined to investigate the mechanism of adsorption process. Coefficient of correlation, r2, and variable error, methods were also applied in the determination of the best fit of the kinetic method. Structural characterization of magnetite coated pine cone and the magnetite coated pine crosslinked to cyclodextrin using 1,6-hexamethylene diisocyanate and epichlorohydrin were confirmed by characterization techniques applied. The adsorption of Cr(VI), As(III) and 4-nitrophenol was found to be dependent on the solution pH, adsorbent dose, initial concentration, temperature and ionic strength. Kinetic modelling revealed that the adsorption of Cr(VI), As(III) and 4-nitrophenol is controlled by pseudo second order kinetic model suggesting surface adsorption and intraparticle diffusion model. Intraparticle, pore and film diffusion models gave further insight into the controlling diffusion mechanism involved in the adsorption process for all pollutants investigated. Equilibrium studies indicated that the adsorption of all pollutants followed Langmuir isotherm indicating that adsorption sites are homogeneous in nature. The obtained thermodynamic parameters demonstrated that the adsorption of Cr(VI), As(III) and 4-nitrophenol were spontaneous, favourable and endothermic in nature. Anionic effect positively affected Cr(VI) and As(III) removal but had a negative effect on the 4-nitrophenol adsorption. Adsorption of 4-nitrophenol onto the nanocomposite adsorbents was attributed to multiple adsorbent-adsorbate interactions such as hydrogen bonding, hydrophobic attraction and guest host interaction. Magnetite coated pine better removed Cr(VI) and As(III) from aqueous solution than NaOH treated pine cone biomaterial while the magnetite coated pine crosslinked to cyclodextrin using 1,6-hexamethylene diisocyanate exhibited better adsorption performance for 4-nitrophenol removal than the nanocomposite crosslinked using epichlorohydrin and the magnetite coated pine cone.
D. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Biosorbent-magnetic; Nanomaterial; Cyclodextrin; Epichlorohydrin; Hexamethylene diisocyanate; Dissertations, Academic -- South Africa.; Water -- Pollution.; Dyes and dyeing -- Textile fibers, Synthetic.; Water -- Purification -- Photocatalysis.